2022
DOI: 10.56294/saludcyt2022151
|View full text |Cite
|
Sign up to set email alerts
|

2D numerical model of downward push pull ventilation for protecting workers against airborne infection

Abstract: Industrial clusters contributed significantly to the spread of Covid-19 worldwide, including in Indonesia. One of the causes is that maintaining a minimum distance of 1 to 2 meters between workers is often challenging due to the plant layout and work system design limitations. Therefore, an intervention to the workstation is needed to protect industrial workers from potential exposure to Covid-19 and other airborne infections. One technology that has a high potential to be applied to solve this problem is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…These results coincide with the reports by Fosso Wamba et al 28 and Xuan Tran et al 29 , who identified a growth in global production in this area, more accelerated since 2014. A similar trend has been observed in other computer science and data science areas, such as the metaverse, which has been recognized as an emerging research area [33][34][35][36] . An expected fact is the predominance of original articles among scientific production; as well in the field of technical sciences, computer science, and health, practice, and experimentation are the ones that generate the greatest contributions.…”
Section: Discussionsupporting
confidence: 76%
“…These results coincide with the reports by Fosso Wamba et al 28 and Xuan Tran et al 29 , who identified a growth in global production in this area, more accelerated since 2014. A similar trend has been observed in other computer science and data science areas, such as the metaverse, which has been recognized as an emerging research area [33][34][35][36] . An expected fact is the predominance of original articles among scientific production; as well in the field of technical sciences, computer science, and health, practice, and experimentation are the ones that generate the greatest contributions.…”
Section: Discussionsupporting
confidence: 76%